Statutory retirement and changes in self-reported leisure-time physical activity: a follow-up study with three time-points - Ansku Holstila; Minna Mänty; Ossi Rahkonen; Eero Lahelma; Jouni Lahti (BMC, 2017)
Abstract Background Retirement is a key life event, which is associated with changes in physical activity, however, there is limited evidence with regard to changes in physical activity that take place in post-retirement years. The aim of this study was to examine how leisure-time physical activity changes shortly after the transition to retirement and during the post-retirement years. Methods The phase 1 data were collected in 2000-2002 (n = 8960, response rate 67%) among 40-60-year-old employees of the City of Helsinki, Finland. Phase 2 was carried out in 2007 (n = 7332, response rate 83%) and phase 3 in 2012 (n = 6814, response rate 79%). Disability retirees and those under the age of 50 at baseline were excluded. This yielded 2902 participants. Most of the participants (79%) were women. The mean age of the participants was 54.4 in phase 1. Negative binomial models for repeated measurements with generalized estimating equations (GEE) were used to calculate the incidence rate ratios (IRR) and 95% confidence intervals (CI). These indicated the changes in time spent in self-reported leisure-time physical activity among the retired compared with the continuously employed. Results Of the participants, 851 retired on the grounds of old age during the first period (phases 1-2), and 948 during the second period (phases 2-3). Change in physical activity was positive among those who retired during the first (IRR = 1.10, 95% CI 1.04-1.17) and second (IRR = 1.10, 95% CI 1.04-1.16) periods compared to the continuously employed. During the second period, there was little difference between those who had retired during the first one (IRR = 0.96, 95% CI 0.91-1.02) and the continuously employed. Conclusions The transition to statutory retirement was associated with an immediate increase in leisure-time physical activity, which nevertheless diminished during post-retirement years.